2022
DOI: 10.3389/fendo.2022.870047
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Glycemic Abnormalities Between Primary Aldosteronism and Essential Hypertension: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe relationship of glycemic abnormalities between primary aldosteronism (PA) patients and essential hypertension (EH) patients is still debatable. This meta-analysis aimed to explore differences in the prevalence of glycemic abnormalities and levels of abnormal glucose metabolism in PA and EH patients.MethodsA search was performed using PubMed, Scopus, Cochrane and Web of Science databases from their inception through January 2022. Inclusion criteria for this study were 1) observational studies whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Studies conducted in several countries have reported prevalence of diabetes in patients with PH ranging between 15.2%-23%[ 3 , 5 , 11 , 15 ]. Two prior meta-analyses reported 1.54-1.55-fold higher risk of glycemic abnormalities with lower marker of insulin secretion and higher insulin resistance in PH compared to essential hypertension (EH)[ 15 , 16 ]. In our PH patients at presentation, we observed high prevalence of diabetes (37.2%) and prediabetes (24.3%), possibly due to higher risk of diabetes in Asian Indian population caused by altered lifestyle, increased visceral fat and insulin resistance with dyslipidaemia[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in several countries have reported prevalence of diabetes in patients with PH ranging between 15.2%-23%[ 3 , 5 , 11 , 15 ]. Two prior meta-analyses reported 1.54-1.55-fold higher risk of glycemic abnormalities with lower marker of insulin secretion and higher insulin resistance in PH compared to essential hypertension (EH)[ 15 , 16 ]. In our PH patients at presentation, we observed high prevalence of diabetes (37.2%) and prediabetes (24.3%), possibly due to higher risk of diabetes in Asian Indian population caused by altered lifestyle, increased visceral fat and insulin resistance with dyslipidaemia[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was excessive auto-secretion of aldosterone in patients with PA, leading to a series of disorders, including metabolic-associated diseases. 3,[5][6][7][8][9][10] As a group of complex metabolic disorder syndrome, MS was a risk factor of cardiovascular disease and also one of the hot spots in PA research. 27 Excessive aldosterone could contribute maturation and dysfunction of adipocytes by combining with…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were uncertain. 7,9,10 As a series of disorganized metabolism, metabolic syndrome (MS) is defined including obesity, elevated BP, glucose metabolism disorders and dyslipidemia. 11 It is evaluated and diagnosed by these indicators: waist circumference (WC), fasting plasma glucose (FPG), BP, triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, Adler et al found that PA patients underwent adrenalectomy or mineralocorticoid receptor antagonist showed the decrease of insulin clearance, which was not due to alterations in creatinine clearance or plasma cortisol [ 6 ]. Fourth, aldosterone could increase hepatic glucose production via increased glucose-6-phosphatase and fructose-1,6-bisphosphatase and phosphoenolpyruvate carboxykinase [ 18 ]. However, the aldosterone levels of the remission or improvement group and unchanged group were not significantly different in our study.…”
Section: Discussionmentioning
confidence: 99%